Functional Resistance Training Superiority Over Conventional Training in Metabolic Syndrome: A Randomized Clinical Trial - Turri-Silva, Natália; Ricci-Vitor, Ana Laura [UNESP]; Cipriano Jr, Gerson; Garner, David; Netto, Jaime [UNESP]; Giacon, Thaís [UNESP]; Destro Christofaro, Diego Giulliano [UNESP]; Marques Vanderlei, Luiz Carlos (Taylor & Francis, 2020)
Metabolic syndrome (MetS) is a growing epidemic related with higher values of blood pressure (BP) and autonomic dysfunction. Scientific evidence has been indicating that functional resistance training (FRT) is superior over conventional (CRT) for muscle fatigue and pain, yet its effects on autonomic modulation (AM), BP and heart rate in MetS are unclear. We theorized that FRT can be superior to CRT in MetS patients because of larger muscle activation. This study compares FRT and CRT on AM, blood pressure, heart rate and muscle strength. Thirty-eight sex and age matched individuals (40 to 60 years) were randomized for FRT or CRT, with training intensity varying gradually from 30%–100% of one maximal repetition test (1MR), 3 times/week for 30 sessions. All outcomes were evaluated at baseline and post training. AM was assessed by heart rate variability (mean RR, RMSSD, SDNN, LF, HF, TINN, RRtri, SD1 and SD2). BP (mmHg) was obtained by cuff measures. Muscle strength was assessed by 1MR. An increase in cardiac parasympathetic activity was observed in individuals allocated to FRT in comparison to CRT group (RMSSD ∆40%; SD1 ∆39%; and HF ms2 ∆80%). Moreover, just FRT was capable of reducing BP post intervention (SBP from 129.21 ± 19.02 to 118.94 ± 14.14 mmHg, p < .009,/d/ = 0.49; DBP from 85.26 ± 11.48 to 77.76 ± 8.93 mmHg, p < .01,/d/ = 0.51). Both groups had a similar increase in muscle strength and no changes between HR. Progressive FRT was more beneficial to CRT regarding AM, increasing vagal activity, and reducing blood pressure in MetS individuals.
Keywords: autonomic modulation; blood pressure; exercise therapy; Metabolic syndrome; resistance training